Dampak Penerapan Undang-Undang Nomor 23 Tahun 2011 terhadap Akuntabilitas Keuangan Pengelola Zakat : (Studi Kasus Badan Amil Zakat Nasional Republik Indonesia) - Rina Nur Izzatin; Syarif Hidayatullah; Hidayat Hidayat (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The financial statements of zakat managers must comply with applicable laws and regulations, namely PSAK number 109 which was declared not to conflict with sharia, and the fatwa of the Indonesian Ulema Council by the MUI National Sharia Council on August 16, 2011. So PSAK number 109 becomes the basic principle in carrying out accounting finance in zakat institutions. All zakat management organizations are required to implement it. The purpose of this study, of them is to analyze the extent to which zakat management organizations obey in preparing financial reports. This research is a type of qualitative research using case studies. The author examines a phenomenon that occurs in the field, namely the many Zakat Management Organizations that have not implemented PSAK number 109. This research is also normative juridical research, namely research that is focused on examining the impact of the implementation of Law number 23 of 2011 on the accountability of zakat managers (a case study of BAZNAS RI), the primary data source comes from the results of interviews, and all regulations related to zakat. Secondary data sources come from official websites, books, and journals. The results of this study indicate that, First, compliance with the preparation of zakat financial reports at zakat management organizations is not yet 100%, as evidenced by the large number of zakat managers who have not implemented PSAk No. 109 that must be implemented by zakat organizations, there are even organizations that have not made zakat financial reports. Second, there are two monitoring mechanisms, namely internal audit, and external audit. The three audits have an important effect on increasing the financial accountability of zakat managers.